Cephalometric effects of the elastodontic appliance in managing skeletal Class II division 1 cases - Ciavarella Domenico; Campobasso Alessandra; Campa Roberta; Suriano Carmela; Illuzzi Gaetano; Cazzolla Angela Pia; Tepedino Michele (Sciendo, 2021)
The aim of the study was to evaluate the cephalometric effects of the elastodontic appliance (EA) in the management of patients presenting with a skeletal Class II/1 malocclusion.